The Analysis of Nascent Entrepreneurs’ Happiness Level in Indonesia - Sitohang, Yosep Oktavianus; Sasmita, Yoga; Andriyana, Yudhie; Pawitan, Gandhi (JDM (Jurnal Dinamika Manajemen), 2017)
This study tried to analyze the factors that influence the happiness level of entrepreneurs in Indonesia especially the nascent entrepreneurs. The level of entrepreneurs’ happiness has a positive effect on the sustainability of their business. The research data are secondary data from 1,148 respondents who are included in the category of Total Early-stage Entrepreneurial Activity (TEA) at Global Entrepreneurship Monitor (GEM) in 2013. The variables employed are motivation, perception and innovation and demographic variables (gender, education and income). Analyzer used is multiple linear regressions with dummy variable. From the result, it is found that only the motivation, education level and level of income that significantly influence the level of happiness. The nascent entrepreneurs, who have motivation to start a business because of opportunity, have a higher level of happiness than necessity motivation due to necessity. The level of education and income are also proportional to the level of happiness, but the level of education gives greater influence to the level of happiness of nascent entrepreneurs in Indonesia.